ANALISIS KETERAMPILAN GURU MEMBIMBING DISKUSI KELOMPOK KECIL DENGAN MENERAPKAN MODEL KOOPERATIF TIPE JIGSAW PADA MATA PELAJARAN IPAS DI KELAS V SDN SE-KECAMATAN HAMPARAN PERAK - Graciela Siahaan, Putri Monica; Siregar, Arifin; Mailani, Elvi; Ananda, Lala Jelita; Siregar, Waliyul Maulana (Jurnal Merah Putih Sekolah Dasar, 2024)
Analysis of Teacher Skills in Guiding Small Group Discussions by Applying the Jigsaw Type Cooperative Model in Social Science Subjects in Class V of Elementary Schools in Hamparan Perak District T.A 2023/2024. Thesis. Medan: Faculty of Education, Medan State University, 2024. This research was carried out with the aim of finding out the level of teacher skills in guiding small group discussions by applying the jigsaw type cooperative model in science and science subjects in class V of SDN in Hamparan Perak District T.A 2023/2024. The research method used is quantitative-descriptive research. The research population consisted of 62 state elementary schools and class V teachers in Hamparan Perak District. The research sample consisted of 6 class V teachers at SDN Hamparan Perak District. Data was collected using observations during three meetings in the learning process, then the data was analyzed using quantitative analysis methods by calculating numbers and then describing them using sentences. The results of the research during three meetings showed that the teacher's skills in guiding small group discussions by applying the jigsaw type cooperative model in the science and sciences subject in class V of SDN in Hamparan Perak District T.A 2023/2024 were in the "very good" category with a percentage of 28% and the category œgood with a percentage of 72%. Based on the results of observations from the three meetings that were held, the six teachers showed improvements which of course varied from the first meeting to the third meeting. Keywords: Skills for Guiding Small Group Discussions, Jigsaw Type Cooperative Model, Teacher.